Tumor microenvironment and cancer metastasis: molecular mechanisms and therapeutic implications - Biray Avci, Cigir; Goker Bagca, Bakiye; Nikanfar, Masoud; Takanlou, Leila Sabour; Takanlou, Maryam Sabour; Nourazarian, Alireza (Frontiers in Pharmacology, 2024)
The tumor microenvironment (TME) plays a crucial role in cancer development and metastasis. This review summarizes the current research on how the TME promotes metastasis through molecular pathways, focusing on key components, such as cancer-associated fibroblasts, immune cells, endothelial cells, cytokines, and the extracellular matrix. Significant findings have highlighted that alterations in cellular communication within the TME enable tumor cells to evade immune surveillance, survive, and invade other tissues. This review highlights the roles of TGF-β and VEGF signaling in promoting angiogenesis and extracellular matrix remodeling, which facilitate metastasis. Additionally, we explored how metabolic reprogramming of tumor and stromal cells, influenced by nutrient availability in the TME, drives cancer progression. This study also evaluated the therapeutic strategies targeting these interactions to disrupt metastasis.By providing a multidisciplinary perspective, this study suggests that understanding the molecular basis of the TME can lead to more effective cancer therapies and identify potential avenues for future research. Future research on the TME should prioritize unraveling the molecular and cellular interactions within this complex environment, which could lead to novel therapeutic strategies and personalized cancer treatments. Moreover, advancements in technologies such as single-cell analysis, spatial transcriptomics, and epigenetic profiling offer promising avenues for identifying new therapeutic targets and improving the efficacy of immunotherapies, particularly in the context of metastasis.